Harmonisasi Sanksi Adat Selaghian Sebambangan Bengkulu Selatan Dengan UU No 16 Tahun 2019 Tentang Perkawinan - Cahaya Dwi Anggola Cahaya Dwi Anggola; Vaula Karera Vaula Karera; Firanica Prawita Firanica Prawita; Jeli Yanti Jeli Yanti; Mardhatillah Mardhatillah (Journal Kompilasi Hukum, 2026)
Selaghian Sebambangan customary sanctions in the Serawai community in South Bengkulu are part of a social control mechanism that functions to maintain family honor, social order, and the balance of kinship relations in traditional marriage practices. Legal problems arise when this practice intersects with national legal provisions regulated in Law Number 16 of 2019 concerning Marriage, especially relating to the minimum age limit for marriage and the obligation to register marriages as a condition for state legal recognition. The focus of the study is directed at the normative construction and legitimacy of Selaghian Sebambangan customary sanctions in the customary legal system of the Serawai community and its relationship with national legal provisions within the framework of Indonesian legal pluralism. The results of the study show that the existence of Selaghian Sebambangan traditional sanctions has strong sociological legitimacy through community acceptance and implementation by traditional institutions through deliberation mechanisms oriented towards the restoration of social relations and family honor. The existence of these customary norms is recognized in the national legal system as long as they do not conflict with the principles of state law and the protection of human rights. Harmonization between customary norms and national law requires harmonization that keeps local wisdom values ​​alive in society, while ensuring legal certainty, orderly administration of marriages, and protection of women and children in the Indonesian legal system. This research also proposes a concrete harmonization model that includes procedural integration, restrictions on customary norms, institutional mediation, and protection of women’s and children’s rights, so that the Selaghian Sebambangan practice maintains cultural values ​​and obtains formal legal recognition